THE EFFECTS OF CYBERCRIME ON NIGERIA’S NATIONAL SECURITY: EVIDENCE FROM GOMBE STATE, NORTH- EASTERN NIGERIA - Ahmed, Usman; Nabil, Yusuf (African Journal of Social and Behavioural Sciences, 2026)
Cybercrime encompasses a wide range of illegal activities, including online fraud, identity theft, hacking, cyber espionage, misinformation and cyber-attacks against individuals, businesses, and government institutions. The challenges posed by cybercrime to Nigeria’s national security are indeed worrisome and thus call for concerted efforts of the major stakeholders across the government agencies. The menace is so obvious that it enormously affects Nigeria’s national security. The study adopts a qualitative research method utilising both primary and secondary sources of data. The primary data were obtained through key informant interviews with fourteen (14) persons purposively selected from relevant agencies and institutions involved in cybercrime and national security. The documentary analysis was equally utilized to augment data obtained from the key informant interview in order to ascertain the validity and reliability of the data collected. The secondary data consist of books, journals, and internet sources. Digital Ecosystem Vulnerability Theory was utilized as a theoretical framework. The study findings reveal that cybercrime is increasing rapidly in Nigeria undetected, affecting its critical national infrastructure, causing prolonged terrorism, and affecting national security. The study recommends that raising public awareness about cyber security risks and best practices ensuring adequate funding for cyber security initiatives, fostering robust partnerships between the government, private sector, and civil society organizations and by uniting these sectors, Nigeria can build a more resilient and secure digital environment that not only protects the country's digital assets but also lays solid foundation for a safer digital future.